2013
DOI: 10.2215/cjn.08770812
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Patients with ESRD and ANCA-Associated Vasculitis in Australia and New Zealand

Abstract: SummaryBackground and objectives This study aimed to evaluate dialysis and transplant outcomes of patients with ESRD secondary to ANCA-associated vasculitis (AAV).Design, setting, participants, & measurements All ESRD patients who commenced renal replacement therapy in Australia and New Zealand between 1996 and 2010 were included. Outcomes were assessed by Kaplan-Meier, multivariable Cox regression, and competing-risks regression survival analyses.Results Of 36,884 ESRD patients, 228 had microscopic polyangiit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 21 publications
3
42
0
3
Order By: Relevance
“…Mortality comparisons accounting for case-mix differences were, again, not performed. With the exception of this subgroup analysis, most other studies examining mortality outcomes after ERSD development in GN were restricted to single GN subtypes (3,(15)(16)(17) or combined subtypes into a single GN category (18,19), precluding direct comparisons across GN subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality comparisons accounting for case-mix differences were, again, not performed. With the exception of this subgroup analysis, most other studies examining mortality outcomes after ERSD development in GN were restricted to single GN subtypes (3,(15)(16)(17) or combined subtypes into a single GN category (18,19), precluding direct comparisons across GN subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…We found 2 studies that directly compared graft and patient outcomes with GPA and MPA. 7,9 The study by Little and associates 7 did not show any difference between GPA and MPA.…”
Section: Pooled Analysesmentioning
confidence: 91%
“…Six studies with a total of 736 kidney recipients reported 10-year survival data. 7,9,18,19,21,24 In these studies, patient survival rates ranged from 64% to 80 % and graft survival rates ranged from 59% to 84%. Four studies 4,17,22,23 and our current study with a total of 103 recipients reported 5-year patient survival of 77% to 100% and graft survival of 60% to 100%.…”
Section: Pooled Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…AAV patients with ESRD on dialysis have a worse prognosis compared to those without dialysis independent renal function [36]. However, the overall mortality of AAV patients on dialysis is similar to those non-diabetic patients on dialysis [37][38][39]. Renal transplantation (RTx) is the first choice of treatment in these patients.…”
Section: Renal Transplantationmentioning
confidence: 99%